Mucopolysaccharidosis Type I in the Russian Federation and Other Republics of the Former Soviet Union: Molecular Genetic Analysis and Epidemiology - Voskoboeva, E. Yu; Bookina, T. M.; Semyachkina, A. N.; Mikhaylova, S. V.; Vashakmadze, N. D.; Baydakova, G. V.; Zakharova, E. Yu; Kutsev, S. I. (Frontiers in Molecular Biosciences, 2022)
Mutations in the IDUA gene cause deficiency of the lysosomal enzyme alpha-l-iduronidase (IDUA), which leads to a rare disease known as mucopolysaccharidosis type I. More than 300 pathogenic variants of the IDUA gene have been reported to date, but not much is known about the distribution of mutations in different populations and ethnic groups due to the low prevalence of the disease. This article presents the results of a molecular genetic study of 206 patients with mucopolysaccharidosis type I (MPS I) from the Russian Federation (RF) and other republics of the former Soviet Union. Among them, there were 173 Russian (Slavic) patients, 9 Tatars, and 24 patients of different nationalities from other republics of the former Soviet Union. Seventy-three different pathogenic variants in the IDUA gene were identified. The common variant NM_000203.5:c.208C>T was the most prevalent mutant allele among Russian and Tatar patients. The common variant NM_000203.5:c.1205G>A accounted for only 5.8% mutant alleles in Russian patients. Both mutations were very rare or absent in patients from other populations. The pathogenic variant NM_000203.5:c.187C>T was the major allele in patients of Turkic origin (Altaian, Uzbeks, and Kyrgyz). Specific own pathogenic alleles in the IDUA gene were identified in each of these ethnic groups. The identified features are important for understanding the molecular origin of the disease, predicting the risk of its development and creating optimal diagnostic and treatment tools for specific regions and ethnic groups.